2009
DOI: 10.1111/j.1399-0039.2009.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA‐A, ‐B, ‐Cw, and ‐DRB1 alleles and haplotypes in an isolated Han population in Southwest China

Abstract: In this study, polymorphisms of human leukocyte antigen (HLA) class I (A, B, and Cw) and class II (DRB1) loci were analyzed in an isolated Han population living in Fengyandong in the Yunnan province of Southwest China (FYDH) using a high-resolution polymerase chain reaction-Luminex typing method. A total of 13 A, 26 B, 15 Cw, and 23 DRB1 alleles of HLA were found in FYDH. The frequencies of A*1101, A*0207, A*2402, B*4601, B*1502, Cw*0102, Cw*0801, DRB1*0901, and DRB1*1202 were >10%. The following haplotypes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…In the Korean population, A*0201 and A*0206, which are E7 [11][12][13][14][15][16][17][18][19] binding alleles, compose 85% of the A2 positive population (79). Among the 16 HLA-A2 alleles that are not predicted to bind E7 [11][12][13][14][15][16][17][18][19] , we find that A*0207, A*0278, A*9208 and A*9217 are found in the Chinese population, with the frequency of A*0207 higher than 10% in the southern Chinese Han population (80,81).…”
Section: Discussionmentioning
confidence: 86%
“…In the Korean population, A*0201 and A*0206, which are E7 [11][12][13][14][15][16][17][18][19] binding alleles, compose 85% of the A2 positive population (79). Among the 16 HLA-A2 alleles that are not predicted to bind E7 [11][12][13][14][15][16][17][18][19] , we find that A*0207, A*0278, A*9208 and A*9217 are found in the Chinese population, with the frequency of A*0207 higher than 10% in the southern Chinese Han population (80,81).…”
Section: Discussionmentioning
confidence: 86%
“…For example, the predominant A-C-B haplotype, A*02:07-C*01:02-B*46:01, was predominant in Vietnamese as well as in some southern Chinese populations, such as the Dai, Hani, Miao, Bouyei, Shui, Han in Yunnan, and Han in Guangdong, but existed at low frequencies in Chinese Hui, Japanese, and Koreans. Another predominant haplotype, A*11:01-C*08:01-B*15:02, was also predominant in Vietnamese and some Chinese populations, such as the Bulang, Dai, Hani, Shui, Han in Yunnan, and Han in Guangdong, who were located in southern China (Tokunaga et al, 1997;Middleton et al, 2004;Chen et al, 2007;Hong et al, 2007;Ogata et al, 2007;Trachtenberg et al, 2007;Hoa et al, 2008;Shi et al, 2008;2010a;2010b;Wen et al, 2008;Yao et al, 2009). Based on the HLA alleles, haplotypes, and neighbor-joining tree analysis, we concluded that the Zhuang is a typical southern Chinese population.…”
Section: Discussionmentioning
confidence: 91%
“…Nei's standard genetic distances among 18 populations were calculated based on HLA-A, HLA-B, and HLA-DRB1 allele frequencies and a neighbor-joining tree was constructed using Mega4.0 software (Tamura et al, 2007). Frequency data for other Asian populations were obtained from previous studies, as follows: Wa and Jinuo (Shi et al, 2008), Bouyei (Imanishi et al, 1992;Chen et al, 2007), Maonan (Ogata et al, 2007), Han in Taiwan (Wen et al, 2008), Han in Hongkong (Hardy et al, 1997), Han in Guangdong (Trachtenberg et al, 2007), Menba (Zhang et al, 2005), Tibetan (Lai et al, 1999;, Hui (Yu et al, 2002;Hong et al, 2007), Han in Beijing (Sun et al, 1997;Deng et al, 2005), Han in Northern (Yang et al, 2006), Dai (Shi et al, 2010a), Han in Yunnan (Yao et al, 2009), and Bulang and Hani (Shi et al, 2010b). Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations